Hungarian students’ carrier aspirations - A.S. Gubik (Marketing i Menedžment Innovacij, 2014)
The article analyzes the students’ carrier aspiration, right after their graduation and five years after their studies. It examines the differences arising from the students’ family business background and their most important social variables (gender, age). Then the study highlights the effects of study field on the students’ intention. The direct effect of education on starting an enterprise is undiscovered in the literature, the paper deals with the influence of availability and services use, offered by higher institutions.